Astronomy and mystic simbols in the Romanesque parish church of Santa Maria in Cortemilia (Cuneo, Italy) - Veneziano, G. (Archaeoastronomy and Ancient Technologies, 2016)
Cortemilia, a town in Piedmont (Italy), is located in an area that in ancient times belonged to Ligurian tribes then conquered by the Romans. At the edge of the town is the Romanesque church of Santa Maria (Sancta Maria de Plebe) of the twelfth or thirteenth century. The magnetic and astronomical survey of church showed an orientation of its axis in the direction of the local rising of the Sun at the Equinoxes. On a wall inside the church is a beautiful sandstone bas-relief. In its center is the Virgin Mary with a crown, sitting on a throne with the baby Jesus on her lap. The measures and overall harmony of the relief reflects the medieval mystic symbolism (the divine Trinity, the Perfection of God, the Virgin and Jesus seen as intermediaries between God and men). In the frame surrounding the Virgin are symbols associated with the stars, among them a Sun that is going to be ?swallowed up? by a sickle-shaped Moon. On manuscripts of the same period we saw that this symbol can be easily attributed to the representation of a total solar eclipse visible from the area of Cortemilia on June 3rd 1239, in the same period when the church was built. It took place more than five centuries after from the previous one: this surely increased the emotional impact of the event of the population, since at that time it was believed there was a close relationship between the total solar eclipses and the omens of divine doom. These feelings are evident also in the written descriptions of that eclipse that came down to us. But also the position of the stars that were visible when the sun was darkened may be the basis of the interpretation of the astral symbols and of their position on the bas-relief: perhaps the anonymous sculptor wanted to ?freeze? on the stone information related to the spectacular astronomical event that he himself had witnessed. The parish church of Santa Maria in Cortemilia and its extraordinary relief are two priceless treasures, a wonderful example of art, culture and astronomical knowledge of the Middle Ages.